Chemical analysis by diffraction: the Powder Diffraction File™. Issue 2 (20th June 2017) - Fawcett, T. G.; Kabekkodu, S. N.; Blanton, J. R.; Blanton, T. N.
Abstract : As we celebrate the 75th anniversary of the Powder Diffraction File, the PDF ® is still a method for chemical and material analyses. The database and embedded software are designed to solve a range of solid-state material analysis problems that includes phase identification, quantitative analysis, crystallinity, and crystallite size measurements. A versatile platform allows users to interpret X-ray, electron, neutron, or synchrotron diffraction patterns for their analyses. Over several decades as diffraction hardware and software continued to improve, the International Centre for Diffraction Data continues to improve the methods and the PDF database, offering unprecedented analysis capabilities to the modern user.